TINJAUAN HUKUM ISLAM TERHADAP SEWA MENYEWA TANAH YANG DISENGKETAKAN DI PULO PISANG KECAMATAN PIDIE - Safwan, Safwan (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
This research was conducted to determine the Islamic law review of disputed land leases in Pulo Pisang, Pidie district. This research uses qualitative methods with data sources consisting of primary data and secondary data. Meanwhile, data collection techniques use observation, interviews and documentation, the data obtained is in the form of primary and secondary data. The research results show that the practice of leasing on disputed land is carried out because it is looking for a middle way to resolve disputes between the legal owner and land users because the disputed land is neglected and not maintained. Review of Islamic law regarding the lease of disputed land in Pulo Pisang, Pidie District, if seen from the Islamic law perspective of disputed land being transferred to lease, this is permissible because of the harm in cases of land disputes. Gampong officials have the authority to mediate disputes that occur in the gampong to provide this solution so that fellow parties do not feel disadvantaged by the dispute